Amplified Charge Transfer for Anionic Redox Probes through Oriented Mesoporous Silica Thin Films. Issue 12 (24th August 2016) - Karman, Cheryl; Vilà, Neus; Walcarius, Alain
Abstract: Diffusion of anionic species through ordered mesoporous silica films is considerably restricted due to electrostatic repulsion by the negatively charged silica surface and this effect is even worse in low ionic strength media (owing to Donnan exclusion effects). This is at the origin of the poor electrochemical response of anionic redox probes at electrodes modified with such mesoporous thin films. Here, by using indium–tin oxide (ITO) electrodes covered with vertically aligned mesoporous silica films generated by electrochemically assisted self‐assembly (EASA), we show that charge transfer for anionic redox probes [i.e. Fe(CN)6 3−/4− ] can be dramatically amplified by using a neutral [ferrocene dimethanol, Fc(MeOH)2 ] or cationic [(Ru(NH3 )6 3+ ] redox mediator. This has been observed by cyclic voltammetry, showing current enhancement in the presence of the mediator, which acts as a mobile electron shuttle between the charge‐excluded Fe(CN)6 3−/4− species from the mesoporous silica film and the underlying ITO surface owing to the ability of the mediator species to diffuse freely through the oriented mesopore channels. This behavior was significantly affected by the relative contents of Fe(CN)6 3−/4− probe to Fc(MeOH)2 mediator, the potential scan rate, and the supporting electrolyte concentration. The most effective improvements were reached at low Fe(CN)6 3−/4− concentration, high mediator content, low potential scan rate, and low ionic strength. Abstract : Excluded by charge : The voltammetric response of charge‐excluded redox anions at mesoporous‐silica‐film‐modified electrodes can be amplified to a significant extent by using charge‐transfer mediators, which are likely to diffuse freely through the mesopore channels and act as an electron shuttle between the electrode surface and the film/solution interface.